Resolving the Covid Vaccination Debate by Understanding Diversity and Standardization. Issue 4 (December 2022) - Li, Shaomin; Selover, David
To help resolve the current debate on whether countries should vaccinate the whole population against Covid, we offer a new perspective by looking at the issue as a case of diversity versus standardization, which, we believe, is at the heart of the issue, moving away from the politics. While diversity and standardization are, to a large extent, opposites, they are also complementary in social, economic and technological development. Over-promoting or artificially suppressing one or the other will harm the creativity and efficiency of an economy. The optimal balance between diversity and standardization is that when facing a new problem of an unknown nature, we must diversify and create a competition to find the best methods for solving it. In the current covid crisis, we have done just that, and now we have a good set of vaccines, some better than others. Once the best methods are found, the government of a country should concentrate and adopt them as the standard for the entire nation for implementation. When we develop vaccines, we need some diversity, a diversity of ideas, approaches and chemistry. Once the best vaccines have been found, we need to have standardization to quickly vaccinate the entire population and realize the benefits of the vaccines.